(3GdeMQQ GdhLjR aj JaSjQ GdcJGH GdYRjRs - (3YHO GdMb Hf ZGdH Hf YHO GdQMef Hf YWjI GdeMGQHj, ef eMGQH bjS, GdZQfGWj, CHh eMeO,J (B542 (3g` s
(3ChdgG (B:s
(3JaSjQ bhdg JYGdi(B:"(3Ef GdPjf jGcdhf CehGd GdjJGei(B" (3ef ShQI GdfSGA s
(3BNQgG (B:s
(3bhdg JYGdi(B:"(3GdPjf jHNdhf hjCeQhf GdfGS HGdHNd(B"(3ef ShQI GdfSGA(B" s
(3GdLRA GdKGdK ef GdfSNI GdSGHYIs
(3bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B282 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B93s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B44 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1613s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs